Analisis Tanggung Jawab Hukum Pembeli Atas Wanprestasi Dalam Transaksi E-Commerce Dengan Metode Pembayaran Cash On Deliver - Ridwan, Abdurrahman Faiz; Diksy, Khoirunnisa Putri; Azzahra, Novita Fitria; Silitonga, Rafhael Roberto; Raynee, Rasheesa Ryash; S, Surahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
At present, the development of technology and information is increasing at the same time as the increasing use of the internet and social media among the public. This can also affect transaction activities in Indonesia. Cash On Delivery or commonly shortened to COD is one of the popular payment methods among Indonesians because it provides convenience for consumers in carrying out transaction activities. However, there are often violations of agreements or defaults committed by buyers, such as refusal of orders without clear reasons or the inability of consumers to pay for goods that have been ordered. This research purposes to conduct a study related to the legal responsibility of the buyer in violation of the agreement or what is commonly called default in electronic commerce transactions or e-commerce using the Cash On Delivery (COD) payment method and analyze how the impact will be on business people and the form of legal responsibility of the buyer in these problems. This research uses a normative juridical research method that focuses on legal analysis through normative studies and laws and regulations. This method also includes collecting information related to positive law, legal principles, doctrines and other legal aspects related to sale and purchase agreements, defaults and e-commerce transactions. The data in this research comes from two types of materials, the first is primary materials, namely the Civil Code (KUH Perdata), Legislation and other Regulations. Meanwhile, secondary materials consist of journals, opinions of experts, and other research results related to the research topic. The results of this study can provide suggestions related to e-commerce transactions, especially for buyers to better understand the legal responsibilities in conducting e-commerce transactions using the Cash On Delivery (COD) method. In addition, a stronger protection system for sellers on social media platform in e-commerce transactions is also needed to deal with various problems of default committed by buyers.